(untitled) (Географический вестник=Geographical bulletin, 2017)
На основе натурных наблюдений и математического моделирования рассматриваются особенности гидродинамического режима Саратовского водохранилища и его влияние на процессы формирования зон неоднородности качества вод во времени и пространстве в условиях суточного регулирования стока. VARIABILITY OF WATER QUALITY IN THE SARATOV RESERVOIR UNDER THE INFLUENCE OF HYDRODYNAMIC PROCESSES The Saratov Reservoir hydro-chemical regime features and their influence on water quality spatial and temporal heterogeneity zones formation processes under the conditions of daily runoff regulation have been considered on the basis of field observations and mathematical simulation.